Sherlock. Season three [videorecording (DVD)] - Gatiss, Mark; Moffat, Steven, 1961- (BBC Worldwide Americas, Inc., 2014)
The question on everyone's lips is finally answered as the hugely popular Sherlock returns in three brand new action-packed adventures. With the demise of Moriarty, Sherlock finds himself locked in another mind battle with the powerful Charles Augustus Magnussen, who is holding the secrets of the world at his fingertips. Once again the game is on for Sherlock Holmes and Dr. John Watson!